2011
DOI: 10.1177/1474022210394141
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of social network sites in relation to intercultural communication

Abstract: This article reports on the results of a project which used a social network site to support students on a year abroad and to foster informal learning, particularly in the area of intercultural communication. The project employed a peer-mentoring structure to solve the problem of role conflict, in which users of these sites may feel some tension as the academic and social dimensions – two contexts usually kept fairly separate – of their lives collide. This article describes how students used the site, reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The results pointed out that social media environments like the Hot Dish application can provide opportunities for young people to engage in debates about socio‐scientific issues and to develop learners' contemporary scientific literacy (Greenhow et al, ). In an out‐of‐academy context, Facebook served as a peer‐mentoring structure that solved the problem of role conflict in an intercultural experience that involved students on a year abroad (Lang, ). Moreover, Facebook proved to be a useful and effective resource for students' group communities in several countries in assisting the users in searching for, analysing and accessing information in self‐initiated activities (Riady, ).…”
Section: Use Of Facebook In Informal Settings Of Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The results pointed out that social media environments like the Hot Dish application can provide opportunities for young people to engage in debates about socio‐scientific issues and to develop learners' contemporary scientific literacy (Greenhow et al, ). In an out‐of‐academy context, Facebook served as a peer‐mentoring structure that solved the problem of role conflict in an intercultural experience that involved students on a year abroad (Lang, ). Moreover, Facebook proved to be a useful and effective resource for students' group communities in several countries in assisting the users in searching for, analysing and accessing information in self‐initiated activities (Riady, ).…”
Section: Use Of Facebook In Informal Settings Of Learningmentioning
confidence: 99%
“…Finally, all of the studies (100.0%) mixed and hybridized the different contexts of learning with no clear‐cut boundaries between contexts (Cassaniti et al, ; Goodyear et al, ; Greenhow et al, ; Idris & Ghani, ; Lang, ; Palmquist & Barnes, ; Pimmer et al, ; Riady, ; Sackey et al, ; Senbel et al, ).…”
Section: Use Of Facebook In Informal Settings Of Learningmentioning
confidence: 99%
“…There is a general agreement in the literature on the statement that SNSs are intended to promote interpersonal connections and interactions among the community (Abu-Shanab & Al-Tarawneh, 2015;Chiroma et al, 2017;Chugh & Ruhi, 2018;Colás-Bravo, Conde-Jiménez, & Martín-Gutiérrez, 2015;Erjavec, 2013;Gafni & Deri, 2012;Gomez et al, 2013;Heo & Lee, 2013;Hershkovizt & Forkosh-Baruch, 2017;Hollyhead, Edwards, & Holt, 2012;Lang, 2012;Seifert, 2016). Considering the teacher-student relationship, the interactions produced within SNSs are usually framed under a constructivism approach.…”
Section: Teacher-student Interaction and Communicationmentioning
confidence: 99%
“…Previous studies have indicated that students' beliefs about content classes may be biased by their perception of the utility of computers in the given learning scenario (Lang, 2012). For example, students may have used technology to reproduce more traditional exercises such as multiple choice or matching type grammar exercises (Ertmer & Ottenbreit-Leftwich, 2010).…”
Section: Jesús García Laborda and Mary Frances Litzlermentioning
confidence: 99%